Building information modelling, integrated project delivery and all that. Issue 1 (3rd January 2017) - Rowlinson, Steve
Abstract : Purpose: This paper aims to review the development of building information modelling (BIM) and integrated project delivery (IPD) in recent years and the process changes that BIM and IPD require. Design/methodology/approach: A qualitative research methodology was applied which involved a comprehensive review of relevant literature leading to a better understanding of the history and development of BIM and IPD. A way forward is suggested for the future development of BIM and IPD. Findings: The research revealed that the IPD approach is already ingrained within certain organisations and their supply chains. The issues of political will and business desire to change the existing procurement systems are examined. The need for fit with regional and national economic and cultural characteristics is a pre-requisite for successful change. Collaborative working, information exchange and trust only exist within the context of a trusted and reliable building information model that all can access, understand and manage. Originality/value: This research pointed out that there is a need to overcome the institutional inertia that besets governments and their agencies and suggested that exemplar institutions and their projects are needed to lead the industry by integrating BIM into IPD through process change.